Integrated Approaches to Poverty Alleviation: Global Perspectives and Strategies - Elisabeth, Cherly (Manunggal Halim Jaya, 2024)
This paper provides a comprehensive analysis of poverty alleviation strategies from a global perspective, synthesizing findings from diverse studies across various countries and contexts. By examining the multifaceted nature of poverty, it highlights the critical role of fulfilling basic needs, the importance of adopting locally specific solutions, and the necessity of inclusive growth and sustainable development. The paper discusses the effectiveness of community-based projects, the impact of education and health on poverty reduction, and innovative funding mechanisms such as the